Thermal and nonthermal behaviors of electron–H2O in presence of laser field - Harish Bohara; Saddam Husain Dhobi; Kishori Yadav; Santosh Kumar Das (Universitas Sebelas Maret, 2025)
Electron–water (H2O) molecule scattering under the influence of laser and thermal fields is a fundamental process in atomic and molecular physics, with significant implications for radiation chemistry, photonics, and quantum control. The interaction of electrons with H2O in the presence of an external laser field modifies the scattering dynamics by introducing additional energy and momentum channels, while thermal effects influence electron oscillations and resonance behavior. Understanding these combined effects is essential for accurately predicting differential cross-sections (DCS) and controlling scattering probabilities in experimental and applied settings, including laser-assisted spectroscopy, nanostructure interactions, and thermally tunable quantum devices. The aim of this work is to study the nature of electron-H2O in presence of laser and heat using scattering technique. For this we desing a theorical model which include thermal wave function, potential of water molecules, S-matrix, Besel function and Kroll-Watson approximation for DCS. The developed model was computed used temperature (293–300 K), scattering angles (0.057°–57°), momentum transfer (0.3–1 eV), distance separation (1–1.5 Å), field strength (0.3–5 a.u.), relative field strength (0.5–2.5 a.u.), electron conductivity (0.1–15 a.u.), polarization (linear, circular, elliptical), and Bessel function order. The computed result shows thermal effects enhance DCS compared to non-thermal conditions (0 K), with resonances observed at specific energies (0.25–1 eV). Higher scattering angles produce larger DCS, while lower angles generate sharper resonances with damping-like behavior. Elliptical polarization yields the highest DCS, followed by circular and linear. Distance separation and electron conductivity modulate constructive and destructive interference patterns, whereas higher-order Bessel functions stabilize DCS, indicating equilibrium between electrostatic interaction and particle rest energy. These findings suggest that controlled temperature and field parameters can manipulate scattering probability in thermal systems.